Exploring health behaviours: understanding drinking practice using the lens of practice theory. Issue 3 (17th December 2019) - Hennell, Kath; Piacentini, Maria; Limmer, Mark
Abstract: Research suggests that there is no safe amount of alcohol but despite this alcohol consumption remains an important part of many [young] people's lives. Viewed as an inherently social activity, drinking alcohol provides an opportunity for socialising and connecting with friends. This study is one of the first to draw on practice theory to explore one type of intoxicated drinking occasion engaged in by young people; framed in this article as a 'proper night out'. This article argues that this hybrid entity is made up of a series of interconnected social practices that have come and now hang together to serve to normalise and routinise intoxicated drinking occasions. The operationalisation of practice theory has enabled an in‐depth exploration of intoxicated drinking and provides the potential for new ways of intervening in harmful drinking practices by refocusing attention away from individual level decision‐making to drinking practices.